Tuning Single-Molecule Conductance by Controlled Electric Field-Induced Trans-To-Cis Isomerisation - Aravena-Ponce, D; Aravena-Ponce, D (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
External electric fields (EEFs) have proven to be very efficient in catalysing chemical reac-tions, even those inaccessible via wet-chemical synthesis. At the single-molecule level, oriented EEFs have been successfully used to promote in situ single-molecule reactions in the absence of chemical catalysts. Here, we elucidate the effect of an EEFs on the structure and conductance of a molecular junction. Employing scanning tunnelling microscopy break junction (STM-BJ) experiments, we form and electrically characterize single-molecule junctions of two tetramethyl carotene isomers. Two discrete conductance signatures show up more prominently at low and high applied voltages which are univocally ascribed to the trans and cis isomers of the carotenoid, respectively. The difference in conductance between both cis-/trans-isomers is in concordance with previous predictions considering π-quantum interference due to the presence of a single gauche defect in the trans isomer. Electronic structure calculations suggest that the electric field polarizes the molecule and mixes the excited states. The mixed states have a (spectroscopically) allowed transition and, therefore, can both promote the cis-isomerization of the molecule and participate in electron transport. Our work opens new routes for the in situ control of isomerisation reactions in single-molecule contacts. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.